Exploring the Impact of Integrated STEAM Education in Early Childhood and Primary Education Teachers - Marcela Silva-Hormazábal; Ángel Alsina (MDPI AG, 2023)
In recent years, Integrated STEAM education has been positioned as an appropriate educational approach to face the challenges of today's society. Nevertheless, to implement this approach in the classroom requires trained and productively teachers. From this perspective, the objective of this article, is to analyse the impact of integrated STEAM education on teachers through their perceptions in a group of 31 in-service Chilean teachers teaching both in early childhood and primary education, with the aim to obtain a diagnosis for the future design of training processes in STEAM. To obtain data, the adaptation of an instrument that evaluates teachers' perceptions of integrated STEM education has been validated. Specifically, three dimensions of this instrument have been analysed: familiarity, attitudes, and confidence of teachers about this educational approach. The results show that: (1) Familiarity: only 6% of the participants consider themselves very familiar with the approach; (2) Attitude: 97% of the participants declare themselves to be very willing or moderately willing to learn more about STEAM; (3) Confidence: the data shows, in general, a moderate level of confidence to implement this approach. In relation to the impact of STEAM integrated education in the Chilean teacher's perceptions, it can be noted that despite the familiarity of the participants is very low, the scenario seems encouraging, because they show a very positive attitude towards this approach, together with a moderate confidence to implement it. Even though these early findings are encouraging, they also show that the teacher's formation is fundamental, because its impact in the teachers, reverberates directly in a positive impact on the students. Consequently, it is necessary to promote the professional development of teachers in STEAM through training programs that improve knowledge about the approach and deliver the necessary tools to implement it in the classroom.